Standardization of technique and screening for salinity tolerance in rice (Oryza sativa L.) - Kumar, Awaneet; Mandal, A B; Sarangi, S K; Verma, R L; Singh, O N (ORYZA-An International Journal of Rice, 2018)
Salt tolerance is an important constrain for rice, which is generally categorized as a typical glycophyte. The present study was carried out at departmental laboratory of Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal, in three replication following CRD. In order to find a suitable dose for screening, initially the seeds of twenty genotypes were subjected to five different concentrations viz., 0 mM, 40 mM, 60 mM, 80 mM and 120 mM of NaCl following glass plate technique for 10 days. The observations were recorded from ten randomly selected seedlings on 12 seedling characters and on the basis of performance of the seedlings of these genotypes grown in all the five concentrations of salt, 60 mM of NaCl was found to be a suitable dose to screen all forty genotypes. All the forty genotypes were further evaluated at 60 mM of NaCl for 14 parameters and respective control in three replications to screen susceptible and tolerant genotypes. Differential growth performances were observed for all the parameters studied. Tolerance index and salinity susceptibility index were found to be reliable parameters in the identification of susceptible and tolerant genotypes. Considering, relative reduction of mean values of seedling characters in general and SSI and TI in particular, six genotypes viz., IR10206-29-2-1-1, PUSA NR 580-6, BRRI Dhan 53, CSR 22, Annada and Lalat were selected as susceptible and IR11T138, Lal Minikit (WGL20471), IR66946-3R-149-1-1, IR06M143, IRRI 147 and BRRI Dhan 47 as tolerant.